Trump administration claims details of mass deportations are state secrets - Olivares, José (The Guardian, 2025)
Justice department avoids providing US judge information on expulsions of Venezuelan immigrants to El Salvador
Keywords: Americas; Donald Trump; El Salvador; Law (US); Trump administration; US foreign policy; US immigration; US news; US politics; Venezuela